2021
DOI: 10.1002/cpp.2643
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of online acceptance and commitment therapy versus compassion‐focused therapy for chronic illness

Abstract: Literature suggests that acceptance and commitment therapy (ACT) is effective in improving well-being and in reducing psychopathological symptoms commonly experienced by people with chronic illness (CI). Compassion-focused therapy (CFT) reduces psychological distress, especially in individuals with high levels of shame and self-criticism, but few studies have explored CFT in CI. Additionally, studies almost exclusively compared ACT and CFT with inactive controls (wait-list; treatment as usual). Also, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…In addition, and while not the focus of the current study, given the acute experiences of threat and trauma reported by COVID-19 survivors (e.g., Tingey et al, 2020 ; Tu et al, 2021 ) and the damaging lasting effects of the disease on their mental health (e.g., depression, anxiety, post-traumatic stress; Liu et al, 2021 ; Taquet et al, 2021 ), it might be relevant to consider the value of compassion-based interventions for these individuals to prevent and address their mental health difficulties and promote their psychosocial well-being. In fact, mounting research has supported the positive effects of compassion-focused interventions for people with chronic or physical illness (e.g., Carvalho et al, 2021 ; Gooding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, and while not the focus of the current study, given the acute experiences of threat and trauma reported by COVID-19 survivors (e.g., Tingey et al, 2020 ; Tu et al, 2021 ) and the damaging lasting effects of the disease on their mental health (e.g., depression, anxiety, post-traumatic stress; Liu et al, 2021 ; Taquet et al, 2021 ), it might be relevant to consider the value of compassion-based interventions for these individuals to prevent and address their mental health difficulties and promote their psychosocial well-being. In fact, mounting research has supported the positive effects of compassion-focused interventions for people with chronic or physical illness (e.g., Carvalho et al, 2021 ; Gooding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third-wave CBT models have been shown to be helpful in other areas where people are experiencing distress in relation to something which is not amenable, possible or ethical to change, and integrative CBT approaches are widely used in health psychology. For example, ACT has been used to support young people with cancer (Clarke et al, 2021), CBT has been shown to be beneficial for supporting children with a range of health conditions (Moore et al, 2019), and CFT has been shown to be efficacious in reducing distress in people with chronic illness (Carvalho et al, 2021). Moreover, it has been suggested that CBT approaches can be beneficial in empowering people in coping with marginalisation and oppression based on their racial and/or ethnic identity, immigration status, socioeconomic status, disability, sexual orientation, gender identity, gender expression, religious identity, language (Dale & Saunders, 2018).…”
Section: Why Cbt?mentioning
confidence: 99%
“…In addition, it should not be assumed that treating objective symptoms (e.g., physiological, behavioral) necessarily reduces subjective symptoms (Taschereau-Dumouchel et al, 2022), such as those related to NeP and anxiety. Looking in more detail at the contributions of this study, the explanatory model of anxiety symptoms suggests the relevance of clinicians reconciling pharmacological treatments (e.g., for NeP) with programs to promote mental health (and prevent/reduce its possible effect on MS) in PwMS, for instance, pain and mood management (see Mohr, 2010) and emotion regulation programs (e.g., compassion-focused therapy, ACT; Carvalho et al, 2022; or emotion-focused therapies, Greenberg et al, 1996).…”
Section: T a B L E 2 Student T-tests Statistics For Anxiety Symptoms ...mentioning
confidence: 97%